Enrichment of HLA Types and Single-Nucleotide Polymorphism Associated With Non-progression in a Strictly Defined Cohort of HIV-1 Controllers - Westrop, Samantha J.; Cocker, Alexander T. H.; Boasso, Adriano; Sullivan, Ann K.; Nelson, Mark R.; Imami, Nesrina (Frontiers in Immunology, 2017)
HIV-1 controllers (HIC) are extremely rare patients with the ability to control viral replication, maintain unchanging CD4 T-cell count and evade disease progression for extensive periods of time, in the absence of antiretroviral therapy. In order to establish the representation of key genetic correlates of atypical disease progression within a cohort of HIV-1+ individuals who control viral replication, we examine four-digit resolution HLA type and single nucleotide polymorphisms (SNP) previously identified to be correlated to non-progressive infection, in strictly defined HIC. Clinical histories were examined to identify patients exhibiting HIC status. Genomic DNA was extracted, high definition HLA typing and genome wide SNP analysis performed. Data were compared with frequencies of SNP in European long-term non-progressors (LTNP) and primary infection cohorts. HLA-B alleles associated with atypical disease progression were at very high frequencies in the group of five HIC studied. All four HIC of European ancestry were HLA-B*57+ and half were also HLA-B*27+. All HIC, including one of self-reported African ethnicity, had the HLA-Cw*0602 allele, and the HLA-DQ9 allele was present only in HIC of European ancestry. A median 95% of the top 19 SNP known to be associated with LTNP status was observed in European HIC (range 78-100%); 17/19 of the SNP considered mapped to chromosome 6 in the HLA region, whereas 2/19 mapped to chromosome 8. The HIC investigated here demonstrated high enrichment of HLA types and SNP previously associated with long-term non-progression. These findings suggest that the extreme non-progressive phenotype considered here is associated with a genetic signature characterised by a single genetic unit centred around the HLA-B*57 haplotype, and the possible additive effect of HLA-B*27.